Borrowing Constraints and the Dynamics of Return and Repeat Migration - Görlach, Joseph-Simon (Journal of Labor Economics, 2023)
As wages in migrant-sending countries catch up with those in destinations, migrants adjust on several margins, including their duration of stay, the number of migrations they undertake, and the amount saved while abroad. This paper combines Mexican and US data to estimate a dynamic model of consumption, emigration, and remigration, accounting for financial constraints. An increase in Mexican household earnings shortens migration duration but raises the number of trips per migrant. For lower-income migrants, a rise in Mexican wages leads to a more than proportional effect on consumption expenditure in Mexico, arising from repatriated savings.